Grapevine double cropping: a magic technology - Lu, Guilong; Zhang, Kai; Que, Youxiong; Li, Yanfeng (Frontiers in Plant Science, 2023)
Grapevine is one of the most important fruit trees in the world, but it is often threatened by various biotic and abiotic stresses in production, resulting in decreased yield and quality. Grapevine double cropping in one year is a kind of preparatory and artificial control technology, which can not only save the loss of natural disasters, but also plays an important role in staggering the peak to market, thus increasing yield and improving the quality of grape fruit. This perspective provides a concise discussion of the physiological basis, the main determinants, and their impacts on yield and fruit quality of grapevine double cropping. We also highlight the current challenges around this theme and prospect its application in the future.